Antimicrobial activity of fingerroot [Boesenbergia rotunda (L.) Mansf. A.] extract against streptococcus mutans and streptococcus sobrinus - Raja Mazlan, R. N. A.; Zakaria, M. P. M.; Rukayadi, Yaya (Oriental Scientific Publishing Company, 2016)
The extract of medicinal plants fingerroot [Boesenbergia rotunda (L.) Mansf. A.] obtained using 100% methanol was tested for antibacterial activity against two major pathogen of dental carries namely Streptococcus mutans KCCM 3309 and Streptococcus sobrinus KCCM 3207. The minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and time-kill curve on S. mutans and S. sobrinus were analyzed using Clinical and Laboratory Standard Institutes (CLSI) methods. Preliminary antimicrobial screening showed the mean zones of inhibition for S. mutans (9.0 mm) and S. sobrinus (8.0 mm). MIC value obtained for S. sobrinus and S. mutans was 313 μg/ml while the MBC values were 313 μg/ml (S.mutans) and 625 μg/ml (S. sobrinus). Time-kill curve were obtained at concentrations of 0xMIC, 1/2xMIC, 1xMIC, 2xMIC, 4xMIC and 8xMIC. S. mutans was found to be more susceptible to the fingerroot extract than S. sobrinus. Time - kill curve showed that the concentration of 8xMIC was able to kill 99.9% of S. mutans after 4 hours treatment. These results may be useful for developing fingerroot B. rotunda as natural anticariogenic agent in toothpaste or any oral care products such as mouthwash in treatment of dental carries, sore throat and flaming gums.